Caracterización del “Centro de transferencia comercial mayorista de Loja, puerto seco”, en el primer semestre del 2024. - Pacheco Velesaca, Cristian Alexander (2024)
The present curricular integration work called Characterization of the “Loja wholesale commercial transfer center, dry port”, in the first half of 2024, characterized socioeconomically by 166 merchants and producers of the transfer center. With the help of study tools, it was possible to geolocate the sector where this center is located. Also, with an observation sheet, it was possible to verify the state of infrastructure, in which, it was located during the first half of 2024. Then, with a socioeconomic survey, created under the needs of the people who work there, the social and economic conditions were identified. Finally, the data obtained from the survey was analyzed, and together with the social indicators, it was created a comprehensible numerical value for the comprehensive analysis of the research. The methodology used to carry out this case study was mixed in nature since qualitative and quantitative data were collected, and using the inductive method it was possible to determine the social and economic conditions that these people present. As a result of the research, it was obtained that the merchants of the transfer center have greater economic solvency, investing significantly more than the small producers, and generating monthly profits of up to 18% of the investment. Consequently, it generates merchants to have a better quality of life compared to producers. In addition, the main products that are offered were determined, such as vegetables, fruits, and legumes, which are part of the basic family basket. The study carried out was presented to the municipal public company Gedes E.P., through an interpretive report for subsequent analysis and dissemination of results if the company requires it.